LEGAL STUDY ON THE TRANSFER OF THE AUTHORITY OF MINING BUSINESS LICENSES TO THE PROVINCIAL GOVERNMENT AND ITS IMPACT ON PRODUCING AREAS (Case Study in North Halmahera Regency) - Selfianus Laritmas; Heltom Sandros Didide (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
With the enactment of Law Number 23 of 2014 concerning local government, there has been a change in the authority to manage mining business licenses between the central government, provincial government and district government. Licensing authority which was originally the authority of the district in accordance with Law Number 32 of 2004 has been dismantled and is now held by the provincial government so as to reduce the role of the district/city government in the management of natural resources such as energy and minerals. The enactment of Local Government Law number 23 of 2014 is contrary to the goal of regional autonomy to bring the government closer to the community, improve public services, and encourage equitable development. With the change in authority, it has resulted in overlap in the arrangement of mining business licenses and the community has made it more difficult to manage licensing in the provincial government. The purpose of this study is to analyze the Granting of Authority by Provincial Regional Governments to Issue Mining Permits and their impact on producing regions, as well as to analyze whether the authority of the provincial local government in issuing mining permits based on Law Number 23 of 2014 concerning Regional Government is appropriate based on the principle of regional autonomy. The research method used is the Normative Juridical Research method. Normative Law research methods or Legal Research are methods or methods used in legal research that are carried out by researching existing literature materials.